2008
DOI: 10.1007/s11999-008-0557-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Anthropometric Patellar Dimensions for TKA in Asians

Abstract: Anthropometric patellar dimensions can influence implant design and surgical techniques in patellar resurfacing for TKA. We measured anthropometric patellar dimensions in 752 osteoarthritic knees (713 in females and 39 in males) treated with TKA in 466 Korean patients and compared them with reported dimensions for Western patients. We investigated the effects of postoperative overall thickness deviations, residual bony thickness after bone resection, and postoperative deviations of component center positions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
53
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 16 publications
(43 reference statements)
7
53
2
Order By: Relevance
“…Another study from the Western population by McHale et al [15] showed similar trend of PA among the male and female genders. It was reported that the patella of Asian population are thinner and smaller than that of the Western subjects [711]. This fact is confirmed in the present study for a South Indian population.…”
Section: Discussionsupporting
confidence: 91%
“…Another study from the Western population by McHale et al [15] showed similar trend of PA among the male and female genders. It was reported that the patella of Asian population are thinner and smaller than that of the Western subjects [711]. This fact is confirmed in the present study for a South Indian population.…”
Section: Discussionsupporting
confidence: 91%
“…Second, the majority of our patients were women (only 10 men were included), which limits the statistical power of our study to detect subtle differences by gender. However, this study was conducted in a consecutive series, and the gender proportion of our study population is similar to other TKA series reported from Korea [15][16][17]. Finally, despite our efforts to obtain radiographs of suitable quality, our study is inherently limited by the use of plain radiographs, eg, by issues such as magnification, limb positional variances, and inability to assess three-dimensional features [20,34].…”
Section: Discussionmentioning
confidence: 69%
“…There are many studies that suggest leaving a minimum patellar thickness of 13 to 16 mm after resection 10,23). Kim et al3) has reported a mean patellar thickness of 21.2 mm and a post-resection thickness of 12.5 mm in 713 female Korean patients. Though there is concern that a thinner resected patella may have increased strain and a higher risk of fracture, Kim et al3) had only one case of periprosthetic fracture in their series, in a patient who sustained it following a fall.…”
Section: Discussionmentioning
confidence: 99%
“…Though patellofemoral complications contribute as one of the main factors responsible for reoperation after total knee replacement (TKR), patellar resurfacing is not generally given as much importance as the femoral or tibial resections by surgeons during TKR 1-3). Due to its small size, variable shape, and lack of distinct anatomical landmarks, osteoarthritic knees in particular, a precise patellar resection is extremely difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation